Drug stockpiling behavior and its impact on anxiety among the general public in the early stage after the lifting of China’s Zero-COVID policy: results from a web-based survey - Huang, Yu; Xu, Shuiyang; Zhao, Xiang; Wang, Lei; Lv, Qiaohong; Wu, Suxian; Wu, Qingqing; Zhang, Xuehai (Frontiers in Pharmacology, 2025)
BackgroundOn 7 December 2022, China lifted most of the restrictions under the so-called zero-COVID policy due to factors like less toxicity of the new variants of the virus, leading to widespread infections throughout China.ObjectivesThis study aims to assess the stockpiling behavior of COVID-19 medicines by the general population in Zhejiang at the early stage after China’s zero-COVID policy cancellation and its impact on people’s anxiety.MethodsA cross-sectional, internet-based survey was conducted to collect information on COVID-19 drug purchasing behavior, sociodemographic characteristics, anxiety levels, etc. Chi-square tests and univariate analyses were used to explore the association between COVID-19 medicines purchasing behavior and sociodemographic characteristics. Multivariate analyses were employed to explore the impact of COVID-19 drug purchasing behavior on anxiety status.ResultsAmong 38,480 participants, stockpiling behavior of COVID-19 medicines was reported by 35.74% of them and was most common among participants from Huzhou area, female, those who aged< 20 years, those with postgraduate education level, health workers. A total of 20,986 (54.54%) participants claimed that they were unable to access any COVID-19 medicines, while 3,742 (9.72%) participants felt it unnecessary to stockpile medicines. The majority of the participants (82.3%) experienced anxiety. Multivariate analyses found that compared to those with severe anxiety, those with moderate anxiety were 1.76 times more likely to have stockpiled COVID-19 medicine (aOR 1.76, 95% CI 1.64-1.89); those with mild anxiety were 2.11 times (aOR 2.11, 95% CI 1.98-2.24) more likely to have stockpiled COVID-19 medicine; those with no anxiety were 2.48 times (aOR 2.48, 95% CI 2.31-2.67) more likely to have stockpiled COVID-19 medicine.ConclusionAt the early stage after China’s zero-COVID policy cancellation, drug stockpiling among the public and the subsequent drug shortage was observed. There exists inequity in distribution between regions and among different groups of people. Many people experienced anxiety, especially those without access to COVID-19 medications. Measures for equitable drug distribution and public education on safe self-medication should be taken for future public health events.